America's communal utopias - Pitzer, Donald E. (University of North Carolina Press, 1997)
From the Shakers to the Branch Davidians, America's communal utopians have captured the popular imagination. Seventeen original essays here demonstrate the relevance of such groups to the mainstream of American social, religious, and economic life. The contributors examine the beliefs and practices of the most prominent utopian communities founded before 1965, including the long-overlooked Catholic monastic communities and Jewish agricultural colonies. Also featured are the Ephrata Baptists, Moravians, Shakers, Harmonists, Hutterites, Inspirationists of Amana, Mormons, Owenites, Fourierists, I.